The method of comprehensive assessment of working conditions in the foundry production - A. M. Lazarenkov; T. P. Kot (Литьë и металлургия, 2021)
The method of a comprehensive assessment of the working conditions of workers in foundries is given. The main production factors of working conditions are determined and a relative complex indicator is introduced that takes into account the considered factors of working conditions. Correction coefficients for each production factor are determined, taking into account their impact on the human body.The equation for calculating the complex indicator was obtained, which made it possible to establish classes of foundries (sections) according to working conditions. The results of calculations of the complex indicator for noise and total for all production factors in foundries with different production patterns are presented.